2023
DOI: 10.1007/s00464-022-09830-6
|View full text |Cite
|
Sign up to set email alerts
|

A duct-to-mucosa pancreaticojejunostomy for small main pancreatic duct and soft pancreas in minimally invasive pancreaticoduodenectomy

Abstract: Background Postoperative pancreatic fistula (POPF) is often associated with significant morbidity and mortality after the Whipple operation. Patient-related factors associated with POPF include soft pancreatic texture and a small main pancreatic duct (MPD). The traditional duct-to-mucosa anastomosis was modified to be easily performed. The aim of the study was to evaluate the simplified pancreaticojejunostomy (PJ) method in the prevention of POPF after minimally invasive pancreaticoduodenectomy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…It has been reported that worse nutritional status can be related to a higher POPF [33]. Additionally, POPF is frequently associated with significant morbidity and mortality following PD, including intraabdominal infection, intraabdominal hemorrhage, a prolonged duration of hospitalization, indications for reoperation or less invasive (radiological or endoscopic) interventional therapy, and mortality [34].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that worse nutritional status can be related to a higher POPF [33]. Additionally, POPF is frequently associated with significant morbidity and mortality following PD, including intraabdominal infection, intraabdominal hemorrhage, a prolonged duration of hospitalization, indications for reoperation or less invasive (radiological or endoscopic) interventional therapy, and mortality [34].…”
mentioning
confidence: 99%
“…In contrast, pancreatic metastasis and serous cystic neoplasm (SCN), a neuroendocrine neoplasm, increase the risk of POPF due to a soft pancreas and small pancreatic ducts [30]. Several surgical pancreaticojejunostomy/pancreaticogastrostomy techniques following PD, as well as pancreatic stump creation or pancreatic transection, have been introduced to reduce the risk of POPF [25,[34][35][36][37].…”
mentioning
confidence: 99%